Building XNA 2.0 Games A Practical Guide for Independent Game Development - Sedlak, John; Silva, James (Apress : Imprint: Apress, 2008)
Building XNA 2.0 Games: A Practical Guide for Independent Game Development is written by James Silva, who recently won the prestigious Microsoft Dream Build Play game competition with his award-winning game, The Dishwasher: Dead Samurai. Building XNA 2.0 Games: A Practical Guide for Independent Game Development is an in-depth and exclusive look into the entire XNA game development process and includes the creation of a software game masterpiece. James Silva guides you through the process he took to build his award-winning title, from concept to reality. He reveals tips and techniques for creating a polished, high-quality game with very few resources, while bridging the gap between coding and art. This title shows software developers the following: The creation of a polished game from start to finish Design philosophies Next-gen 2D graphics, including shaders Techniques for fast, fluid game play XACT Audio and XInput Eye-catching particle effects for visual stimulation The book is packed full of code, pictures, and valuable insights into XNA game development.